2017
DOI: 10.1021/acs.nanolett.7b00249
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Sulfur Impregnation of Microporous Carbon Accelerated by Nanoscale Interfacial Effects

Abstract: Impregnation of porous carbon matrices with liquid sulfur has been exploited to fabricate composite cathodes for lithium−sulfur batteries, aimed at confining soluble sulfur species near conducting carbon to prevent both loss of active material into the electrolyte and parasitic reactions at the lithium metal anode. Here, through extensive computer simulations, we uncover the strongly favorable interfacial free energy between liquid sulfur and graphitic surfaces that underlies this phenomenon. Previously unexpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 34 publications
3
23
2
Order By: Relevance
“…Generally, pore with pore diameter less than 2 nm and total surface area greater than 1000 m 2 g −1 is referred to as micropore Microporous carbon with stable electrochemical properties and high specific surface area receives extensive interest in the field of LSBs As a conductive substrate, microporous carbon can not only load more elemental sulfur and enhance the utilization of active materials but also physically confine polysulfides due to its excellent structure in charge/discharge process …”
Section: Porous Carbonsmentioning
confidence: 99%
“…Generally, pore with pore diameter less than 2 nm and total surface area greater than 1000 m 2 g −1 is referred to as micropore Microporous carbon with stable electrochemical properties and high specific surface area receives extensive interest in the field of LSBs As a conductive substrate, microporous carbon can not only load more elemental sulfur and enhance the utilization of active materials but also physically confine polysulfides due to its excellent structure in charge/discharge process …”
Section: Porous Carbonsmentioning
confidence: 99%
“…The nanosphere walls are porous; BET analysis revealed that pore sizes range from 1 to 1.3 nm. 22 After sulfur impregnation, SEM and EDS was performed. Figure 1b shows a typical SEM image of the S 8 (w = 0.6)/C materials with a magnified image in the inset.…”
Section: Resultsmentioning
confidence: 99%
“…To tackle these issues, various strategies have been proposed in the literature such as highly engineered sulfur cathodes, protected Li anodes, interlayers in the cell structure, solid- or liquid-state catalysts, lower-solubility electrolytes, and so forth. Particularly, carbonaceous materials with excellent electronic conductivity and large specific surface area could significantly improve the cell performance when they were implemented in sulfur cathodes. Therefore, various carbonaceous materials like hollow nanospheres, nanofibers/nanotubes, nanosheets, graphene, carbon papers and cloths, and so forth have been investigated. Carbon papers and cloths were also used as interlayers between the sulfur cathode and Li anode in the cell structure, which effectively prevented irreversible loss of polysulfides. However, most carbonaceous materials showed poor chemical affinity for the sulfuric moieties (i.e., low sulfiphilic properties), and thus, carbonaceous materials could not effectively prevent the loss of polysulfides into the electrolyte followed by the shuttle effect or irreversible capacity decay .…”
Section: Introductionmentioning
confidence: 99%